Enhancing Religious Literacy as a Strategy for Developing Digital Ethics among the Younger Generation on Social Media - Radila, Gustina; Januar, Exsaris; Dahliana, Dina; Suhendra, Yoga; Mandaria, Vilsa (International Journal of Elementary School, 2025)
This study aims to analyze the contribution of religious literacy to shaping young people's digital ethics on social media platforms. The research employs a qualitative approach, using data collection techniques such as in-depth interviews and participant observation with groups of teenagers active on several social media platforms. The findings indicate that enhancing religious literacy provides a strong moral foundation and ethical values, which in turn encourage more responsible and ethical digital behavior among the younger generation. The implications highlight the importance of integrating religious literacy education into learning programs and social activities related to social media use, in order to foster a positive and dignified digital environment and support the character development of an ethically conscious younger generation.